2012
DOI: 10.1021/ct200873y
|View full text |Cite
|
Sign up to set email alerts
|

Designing Short Peptides with High Affinity for Organic Molecules: A Combined Docking, Molecular Dynamics, And Monte Carlo Approach

Abstract: We present a method for designing artificial receptors capable of binding with high affinity to a chosen target organic molecule. The primary sequence of the peptide is optimized to maximize its binding affinity. Our algorithm builds on a combination of molecular dynamics, semiflexible docking, and replica exchange Monte Carlo and performs simultaneous sampling in sequence and conformational spaces carefully selecting the degree of flexibility in the mutated peptides. The approach is used to design a decapepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Higher affinity has been reached by an algorithm based on a combination of molecular dynamics, semiflexible docking using Autodock Vina, and replica exchange Monte Carlo (REMC[ 36 ]). Using this protocol a deca-alanine was shown to evolve to a final sequence showing nanomolar affinity towards the antiretroviral drug efavirenz[ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher affinity has been reached by an algorithm based on a combination of molecular dynamics, semiflexible docking using Autodock Vina, and replica exchange Monte Carlo (REMC[ 36 ]). Using this protocol a deca-alanine was shown to evolve to a final sequence showing nanomolar affinity towards the antiretroviral drug efavirenz[ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…We use the Vina-based approach of Ref. [ 37 ] (descibed in Fig 1A ), that successfully generated drug recognizing peptides of nanomolar affinity, to generate a number of protein binding peptides. We chose the maltose binding protein (MBP, Fig 1B ) as a test case and a set of peptides computationally designed to bind to its maltose binding site.…”
Section: Introductionmentioning
confidence: 99%
“…NPs provide with high local density of receptor to enhance analyte binding and detection (de Miguel and Sanders, 1998; Snowden and Anslyn, 1999; Wiskur and Anslyn, 2001; Wright et al, 2005; Späth and König, 2010) and can enforce multiplexing capability (Griss et al, 2014). Similar approaches to capture attomolar concentration of methylmercury with gold nanoparticle-enhanced electrodes have recently been shown by Cho et al (Hong Enriquez et al, 2012) and other groups showed promising results with other toxic cations in solution (Liu et al, 2011; Cho et al, 2012), via electronic or electrochemical read-out technologies.…”
Section: Perspective On Application Of Nanotechnology In Developing Pmentioning
confidence: 62%
“…Successful examples of tailored synthetic receptor are extremely promising. A synthetic peptide receptor showed excellent sensitivity in detecting methotrexate, an anti-cancer drug, in a miniaturized test that could be re-engineered for other pharmacological molecules (Griss et al, 2014), and bioinformatics efforts provides in silico screening of peptide with high affinity for selected target molecules (Hong Enriquez et al, 2012). These kinds of compounds may be repurposed for a library of specific anti-AED (and other drug) receptors providing extreme flexibility in the panel of drug that can be monitored with portable techniques.…”
Section: Perspective On Application Of Nanotechnology In Developing Pmentioning
confidence: 99%
“…We designed 16-residue long peptides following the procedure described in Gladich et al 2015. In order to reduce the entropic penalty in the unbound state, we designed cyclic peptides (Hong et al 2012) keeping a disulfide bridge between the first and the last cysteine residues of the ring. Additional details on the computational procedure are reported in the Materials and methods section.…”
Section: Resultsmentioning
confidence: 99%